Evaluasi Proses Pembelajaran IPA Biologi Berbasis Scientific Approach pada Materi Pencemaran Lingkungan Kelas VII di SMP Muhammadiyah se-Kecamatan Mergangsan Yogyakarta - Anggraini, Agustina Novita; Aprilia, Nani (STKIP PGRI Bandar Lampung, 2020)
This study aims to evaluate the learning process of Biological Science on Environmental Pollution material in class VII Muhammadiyah Junior High Schools in Mergangsan sub-district with a scientific approach. This type of research is evaluation research. The data obtained were analyzed descriptively quantitatively. The results of the study are as follows: 1) The learning process with a scientific approach at SMP Muhammadiyah in Mergangsan sub-district is in accordance with Permendikbud No.103 2014 and Permendikbud No. 22 of 2016. 2) The learning process with the application of the scientific approach at SMP Muhammadiyah in Mergangsan sub-district, the aspects of preliminary activities get a percentage of 76.69% in the